(untitled) (Research, Society and Development, 2021)
This article aims to analyze the new sanitation framework and the possible impacts on small Brazilian municipalities. Therefore, a study of the entire bibliography already published was carried out, in the form of magazines, books, written press and separate publications. The results showed that the new sanitation framework represents a setback from the point of view of social rights, since it stimulates the mercantilist logics in the management of water and sanitation services. Experiences in the world show that universalization is not possible without democratic management and the contribution of public resources. The conclusion is reached that private companies will prioritize rich cities, forgetting small municipalities, as private companies are guided by profit, because this is the reason for their activity. In this aspect, the New Marco may have more doubts and obstacles than certainties. Furthermore, in Law No. 14,026 of 2020, there are several unconstitutional articles that affect the autonomy and organization of municipalities and affect the federative pact. In this context, there are several Direct Unconstitutionality Actions with the STF so that the New Sanitation Framework is declared incompatible with the Brazilian legal system. In this way, the aim is to ensure that basic sanitation services are offered exclusively by the government. This is because the main purpose of this power is to act in favor of the collectivity.